Fixed and Modifiable Correlates of Drug-Eluting Stent Thrombosis From a Large All-Comers Registry: Insights From ADAPT-DES. (October 2015) - Brodie, Bruce R.; Garg, Ankit; Stuckey, Thomas D.; Kirtane, Ajay J.; Witzenbichler, Bernhard; Maehara, Akiko; Weisz, Giora; Rinaldi, Michael J.; Neumann, Franz-Josef; Metzger, D. Christopher; Mehran, Roxana; Parvataneni, Rupa; et al.
Abstract : Background—: Previous studies evaluating correlates of stent thrombosis (ST) have included mostly patients with bare metal stents and early-generation drug-eluting stents (DES) and have not systematically evaluated the role of intravascular ultrasound–guided stenting and high platelet reactivity on clopidogrel. The purpose of this study was to evaluate the frequency and correlates of ST in patients receiving DES, specifically examining the impact of risk factors modifiable by physician and patient behavior. Methods and Results—: Assessment of Dual Anti-platelet Therapy With Drug-Eluting Stents (ADAPT-DES) was a multicenter, prospective study in patients undergoing successful coronary intervention with DES in whom routine platelet reactivity testing was performed. Definite or probable ST occurred in 92 (1.1%) of 8582 patients within 2 years. Independent baseline correlates of ST included presentation with an acute coronary syndrome (hazard ratio [HR]=1.81, P =0.01), insulin-treated diabetes mellitus (HR=1.91, P =0.02), previous myocardial infarction (HR=1.75, P =0.02), and peripheral arterial disease (HR=2.01, P =0.01). Independent treatment-related correlates included use of early generation DES (HR=1.75, P =0.02), no procedural intravascular ultrasound guidance (HR=1.75, P =0.04), and premature discontinuation of dual antiplatelet therapy (HR=2.67, P =0.003); high platelet reactivity on clopidogrel trended as a correlate of ST (HR=1.49, P =0.08). The 2-year risk of ST ranged from 0.3% to 10.0% when 0 to 3 modifiable risk factors were present. Conclusions—: After successful DES implantation, ST occurred within 2 years in 1.1% of patients and was strongly associated with fixed and modifiable risk factors. The frequency of ST may be reduced with intravascular ultrasound –guided stenting, assiduous adherence to dual antiplatelet therapy, and adequate P2Y12 platelet receptor inhibition. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00638794. Abstract : Supplemental Digital Content is available in the text.